2020
DOI: 10.1371/journal.pone.0240510
|View full text |Cite
|
Sign up to set email alerts
|

ZnO and TiO2 nanoparticles alter the ability of Bacillus subtilis to fight against a stress

Abstract: Due to the physicochemical properties of nanoparticles, the use of nanomaterials increases over time in industrial and medical processes. We herein report the negative impact of nanoparticles, using solid growth conditions mimicking a biofilm, on the ability of Bacillus subtilis to fight against a stress. Bacteria have been exposed to sublethal doses of nanoparticles corresponding to conditions that bacteria may meet in their natural biotopes, the upper layer of soil or the gut microbiome. The analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The proteomic study showed a dramatic change of the metabolic pathways in Bacillus subtilis exposed to ZnNPs (0.017 mg/mL, 100 nm, Sigma Aldrich). Major changes have been observed in methylglyoxal and thiol metabolisms, oxidative stress and stringent responses ( 167 ). As some researches have suggested, the effect of NPs on microorganisms is dose- and time-dependent, so the impact of ZnNPs should be carefully considered to maintain balance in the environment ( 167 ).…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…The proteomic study showed a dramatic change of the metabolic pathways in Bacillus subtilis exposed to ZnNPs (0.017 mg/mL, 100 nm, Sigma Aldrich). Major changes have been observed in methylglyoxal and thiol metabolisms, oxidative stress and stringent responses ( 167 ). As some researches have suggested, the effect of NPs on microorganisms is dose- and time-dependent, so the impact of ZnNPs should be carefully considered to maintain balance in the environment ( 167 ).…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
“…Major changes have been observed in methylglyoxal and thiol metabolisms, oxidative stress and stringent responses ( 167 ). As some researches have suggested, the effect of NPs on microorganisms is dose- and time-dependent, so the impact of ZnNPs should be carefully considered to maintain balance in the environment ( 167 ). Other research has been focused on the interaction of ZnNPs with cell membrane of probiotic bacteria strains.…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
“…The data acquisition parameters of the mass spectrometer used: integration time 0.9 s per channel or 2.7 s per m/z (3 channels out of 20 available were monitored). Monitored masses (natural isotopic abundance, %): 27 Al (100%), 45 Sc-internal standard abbreviated ISTD (100%), 47 Ti (7.44%), 48 Ti (73.22%), 64 Zn (48.63%), 66 Zn (27.90%), 66 Zn(18.75%), 89 Y-ISTD (100%), 209 Bi-ISTD (100%). Calibration standards were acquired to represent the calibration curves for each isotope (6 concentrations per element: 0.0001%, 0.001%, 0.01%, 0.1%, 1%, and 10% of the spike concentration, in order, from the most diluted calibration standard to the most concentrated one.…”
Section: Characterizationsmentioning
confidence: 99%
“…It is highly challenging for bacteria to develop resistance to nanoparticles because they operate against bacterial cells in several ways at once. The antibacterial activity of nanoparticles varies according to their type: nanoparticles like TiO 2 and ZnO affect bacterial cells mostly by binding the bacterial cells and generating ROS [64,66]. The bacterial response to the activity exerted by nanoparticles is also influenced by a series of factors like their number, shape, charge, size, and their mode of action.…”
Section: Agar Disk-diffusion Test On Nafcillin-loaded Samplesmentioning
confidence: 99%
“…However, the broad usage of sunscreen products containing NPs has gradually raised concerns regarding their potential toxicity, and the controversy over the safety of NPs for human skin has never disappeared [12,13]. Major questions regarding the safety of ZnO NPs in sunscreens were related to their toxic potential in human umbilical vein endothelial cells (HUVECs), epidermal cells (A431), viable human keratinocytes, and fibroblasts, and it was demonstrated that ZnO NPs can induce cytotoxicity [11], oxidative stress [14] and DNA damage to skin [15].…”
Section: Introductionmentioning
confidence: 99%